The induction of oocyte maturation and ovulation in the European eel (Anguilla anguilla): in vitro and in vivo comparison of progesterone with 17α,20β-dihydroxy-4-pregnen-3-one - Jéhannet, Pauline; Palstra, Arjan P.; Meijerhof, Miriam; Schipper, Henk; Giménez, Ignacio Nebot; Dirks, Ron P.; Swinkels, William; Heinsbroek, Leon T. N.; Komen, Hans (Frontiers in Physiology, 2023)
Ovulation in European eel is induced by injection of 17α,20β-dihydroxy-4-pregnen-3-one (DHP) as the maturation-inducing hormone (MIH). Female eels need to ovulate within 18 hours after injection to release good quality eggs. Progesterone (P), as an upstream precursor of DHP, may promote endogenous DHP production and improve egg quality. The purpose of this study was therefore to compare treatment of P with DHP on batch level, in vitro, to determine dose-response effects, and in vivo, at a single dose. For the in vitro experiment, ovarian tissue was extracted and placed in culture plates containing hormone-free medium and media supplemented with the treatment: DHP at 1, 10 and 100 ng.mL-1, or P at 10, 100 and 1,000 ng mL-1. At the start of incubation, the folliculated oocytes were sampled for histology, microscopy and qPCR. After incubation for 12 and 18 h, the oocytes were sampled for microscopy and qPCR analysis. For the in vivo experiment, females were either injected with DHP or P at a dose of 2 mg kg-1 to assess their effects on ovulation and reproductive success. At the moment of release, eggs were sampled for RNA sequencing to compare effects of DHP and P on the expression of genes involved in egg quality aspects. Remaining eggs were fertilized and larval viability was recorded. Both DHP and P were able to induce GVBD (DHP at 10 and 100 ng mL-1, P at 100 and 1,000 ng mL-1) in vitro. Expression of genes involved in oocyte maturation and ovulation was similar in vitro for both DHP and P treatments. Regarding the in vivo results, RNAseq results reflected similar DHP and P effects on the expression of genes involved in egg quality aspects. Females injected with either DHP or P ovulated, released eggs, and were equally able to produce larvae without any differences in reproductive success. Our results support the conclusion that DHP and P work equally well in vitro and in vivo. P is more attractive to apply as the price is 3,000 times lower than the price of DHP.